Meningkatkan Motivasi Peserta Didik Melalui Model Problem Based Learning Berbantuan Media Audiovisual di Fase C Kelas 5 SDN 040519 Tanjung Barus - Elisabet Br Tarigan (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to enhance student learning motivation through the implementation of the Problem Based Learning (PBL) model supported by audiovisual media in the fifth grade of SDN 040519 Tanjung Barus. The method used is classroom action research, consisting of two cycles, with each cycle including planning, implementation, observation, and reflection. Data were collected through observations, questionnaires, and interviews to evaluate student motivation before and after the PBL model implementation. The results indicate that the application of the PBL model significantly improves student learning motivation, as reflected in increased active participation in discussions, a desire to complete assignments, and positive responses to feedback from teachers. The average motivation score increased from 65% in the first cycle to 85% in the second cycle, demonstrating that the applied learning strategy was successful. This study provides important contributions to the development of more engaging and relevant teaching methods and offers recommendations for teachers to integrate audiovisual media into the learning process to enhance student motivation and engagement.